Checklist of the Ebenaceae of Equatorial Guinea - Bruno Senterre (Anales del Jardín Botánico de Madrid)
A list of the Ebenaceae collected by the author (158 specimens) or reported from Equatorial Guinea is presented. There are 25 identified species, including 12 new records for the country. After considering their distribution area and habitat, two species previously reported from Equatorial Guinea are excluded, and the presence of seven further taxa is considered highly probable. Diospyros cinnabarina and D. simulans are considered independent species. Formal description of two new taxa is delayed until better material can be collected.